Women University Presidents: Learning through Leadership Development Programs - Christiana Horn (Adult Education Research Conference, 2018)
Women administrators face a number of challenges in their pursuit of a university presidency. Leadership development programs provide valuable learning experiences that strengthen their potential of becoming a university president.
Keywords: women university presidents; leadership development